An experimental study of the impact of a sepak takraw ball on a flat surface - Ahmad, N.; Taha, Z.; Ujihashi, S.; Tanaka, K. (2009)
The takraw ball is a very unique interwoven ball used in the action game of sepak takraw. To date there has been no studies on the dynamic behavior and mechanical properties of the takraw ball. The purpose of this study is to predict the dynamic behavior and mechanical properties of the takraw ball in particular of normal impact on flat surfaces at low speeds. Two methods are employed to measure the dynamics behavior and mechanical properties of the takraw ball. The impact force, contact time, coefficient of restitution, deformation of the ball, inbound and rebound velocity were measured by using two dimensional motion analysis of high-speed video data and force plate data. Then, a finite element (FE) model of the homogeneous takraw ball is constructed, based on the experimental results. This FE model is used to predict modulus elasticity and Poisson ratio of the takraw ball. The FE analysis solution of the ball model was found to be reasonable close with the experimental results. However further improvement need to be done by taking into consideration the nonlinearity of the takraw ball under large deformation as well as at high impact velocity.